Leuit and prohibition forest: Indigenous knowledge of an Urug community resilience - Bahagia Bahagia; Fachrudin Majeri Mangunjaya; Rimun Wibowo; Zulkifli Rangkuti; Muhammad Azhar Alwahid (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
This research aimed to investigate the function of leuit and prohibition forest based on indigenous knowledge of Urug people for combating climate change toward community resilience. The research method used an ethnographic qualitative approach. This method was related to local cultural, ritual, and traditional communities, the data collected through in-depth interviews, observation, and documentation. The selection of sample as informant exert purposive sampling technique. The result is probed meticulously through triangulation technique and triangulation sources. The result shows that traditional storage (leuit) has a role in confronting climate change and disaster and life perturbance for achieving community resilience. Another finding is Urug people create a prohibition forest. The impact is the wood can rescue from damage. The community can fight climate change, get adequate water, and environment preservation.